Batteries: High Sulfur Loading in Hierarchical Porous Carbon Rods Constructed by Vertically Oriented Porous Graphene‐Like Nanosheets for Li‐S Batteries (Adv. Funct. Mater. 48/2016). (December 2016) - Zheng, Zongmin; Guo, Hongchen; Pei, Fei; Zhang, Xin; Chen, Xinyi; Fang, Xiaoliang; Wang, Taihong; Zheng, Nanfeng
Abstract : As X. L. Fang, N. F. Zheng and co‐workers demonstrate on page 8952, 3D hierarchical porous carbon rods constructed by vertically oriented porous graphene‐like nanosheets (HPCR) serve as ideal host materials for high sulfur loading. Li‐S batteries employing the HPCR/S composite with 88.8% of sulfur exhibit a high energy density, excellent rate performance, and good cycling stability.